Trace element and mercury speciation analysis in yerba mate (Ilex paraguariensis) - María Victoria Panzl; Jarol R. Miranda-Andrades; Wendy J. Sandoval Rojano; Joseane A. Mendes; Tatiana D. Saint'Pierre; Alejandra Rodríguez-Haralambides; Ricardo Q. Aucelio (Journal of Trace Elements and Minerals)
Background: Yerba mate, a popular beverage in South America, is rich in bioactive compounds and minerals. However, yerba mate leaves may contain toxic metals and environmental contaminants. This study performed multi-element analyses using ICP-MS and ICP OES and mercury speciation by GC-CV-AFS and CV–AAS to profile infusions of ten yerba mate samples consumed in Brazil and Uruguay. Materials and methods: For ICP OES and ICP-MS analyses, 500 mg infusions of samples were prepared and diluted with 10 % v/v HNO3. Ultrasonic-assisted extractions of mercurial species were made followed by distillation and dilution with water for CV-AAS. For GC-CV-AFS speciation, samples were extracted and distilled, using 200 μL aliquots for analysis. Results: The most abundant elements in the digested solid samples were K, Ca, and Mg, whereas in infusions the ranges were up to 9.18 mg g−1 for K, 0.68 mg g−1 for Ca, and 2.74 mg g−1 for Mg. Pb presented a mean concentration of 260 µg kg−1 in leaves but it was not found in infusions. Hg2+ was found from 0.67 to 0.96 μg kg−1 in leaves with one sample presenting 0.67 μg kg−1 of CH3Hg. Conclusion: K, Ca, and Mg were the most abundant elements in the yerba mate samples. Four samples showed ultra-trace concentrations of Hg2+ and one of CH3Hg.